2019
DOI: 10.1111/ilr.12148
|View full text |Cite
|
Sign up to set email alerts
|

The link between economic and social upgrading in global supply chains: Experiences from the Southern Cone

Abstract: This article uses nine case studies of global supply chains (GSCs) in Southern Cone countries to explore the extent to which economic and social upgrading are linked and spread from lead firms to their supply chain. While economic and social upgrading are found in lead firm segments throughout the case studies, the impacts on suppliers are varied. Pattern groupings enable the authors to develop a three‐part typology of development in GSCs, in the light of which they consider the roles of public policies, compa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 26 publications
1
4
0
Order By: Relevance
“…Lastly, in the analysis of influencing factors, panel regression results show that top-down government governance, environmental regulation, and the strength of the state economy can effectively promote the coordinated development of local economic, social, and environmental upgrading, partially confirming existing research [27,88]. Additionally, the level of foreign investment also effectively fosters the development of local economic, social, and environmental upgrading, aligning with previous study conclusions [32][33][34].…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…Lastly, in the analysis of influencing factors, panel regression results show that top-down government governance, environmental regulation, and the strength of the state economy can effectively promote the coordinated development of local economic, social, and environmental upgrading, partially confirming existing research [27,88]. Additionally, the level of foreign investment also effectively fosters the development of local economic, social, and environmental upgrading, aligning with previous study conclusions [32][33][34].…”
Section: Discussionsupporting
confidence: 82%
“…Existing studies primarily focus on the impact of economic globalization and local governance as key influencing factors. It has been observed that foreign direct investment positively affects all three forms of upgrading [32][33][34]. Specifically, variations in supply chain governance models can yield distinct outcomes in social, economic, and environmental upgrading [35,36].…”
Section: Literature Reviewmentioning
confidence: 99%
“…In tracing the impact of digital labour platforms on global inequalities, we face a similar set of context-contingent issues addressed in research on global value chains (GVCs) (e.g. Reinecke and Posthuma, 2019). While the new work opportunities provided on a digital platform (or by a GVC supplier firm) may in many countries be more attractive than the next best domestic alternative, they are unlikely to offer anything like the standard of remuneration paid in the home country of the business client – although country context (institutions, gender relations, legal compliance and trade unions) matter very much (Barrientos, 2019).…”
Section: New Technologies: Job Losses Inequalities and Precarious Workmentioning
confidence: 99%
“…For example, in a recent very useful typology, Reinecke and Posthuma (2019) show that positive examples of lead GSC business practices involve 'integrated upgrading', where lead firms support upgrading among suppliers in the form of training, health and safety or production organisation. Negative examples, on the other hand, are characterised as 'truncated development' or 'oppositional development', in which a lead firm's economic gains are won at the expense of adverse outcomes for the supplier, whether poor working conditions or environmental externalities.…”
Section: Global Supply Chainsmentioning
confidence: 99%